Peran Pemberdayaan Masyarakat dalam Penguatan Ketahanan Keluarga - Mutmainah, Nur Fitri; Saharuddin, Erni; Utsany, Royan; Warastri, Annisa (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
This community service activity is based on the background of  the family vulnerability that is in Dukuh Karangtengah with indicators of the rate of divorce, cause juvenile delinquency, increased cases of stunting. The importance of the family resilience aspect is needed as a promotional and preventive effort against such problems. The purpose of this PkM activity is to enhance the knowledge, skills of the community partners in promoting strengthening family resilience. The objective of this activity is the realization of the independence of the society in connection with social, economic and health aspect. The method is carried out with knowledge education, as well as training related to strengthening community groups, strengthening institutions with hydroponic skills and cultivation of catfish program. Based on statistical, there is a significant improvement in the average of knowledge before and after education and training. This family resilience-building activity is important to realize the national resiliencia in a wider way.